(untitled) (Journal of Pathology of Nepal, 2025)
Intrathyroidal parathyroid carcinoma is an exceptionally rare and often underrecognized malignancy arising from the parathyroid glands located ectopically within the thyroid gland, usually posing a diagnostic and therapeutic challenge due to its overlapping clinical and pathological features with benign parathyroid adenomas, hyperplasia, and other thyroid neoplasms. Despite advancements in diagnostic imaging and histopathological techniques, the incidence of intrathyroidal parathyroid carcinoma remains low, and much of the current knowledge is based on case reports and small series, highlighting the need for a consolidated review of its clinical course, diagnostic criteria, and management strategies. We report a case of a 60-year-old female presenting with midline neck swelling, which was diagnosed as intrathyroidal parathyroid carcinoma based on histopathology and immunohistochemistry, along with a detailed review emphasizing its clinical features, diagnostic approaches, and management strategies, while identifying areas for future research to elucidate this enigmatic malignancy better.